Fluoride-free and nitrate-free cast iron enamel low temperature ground coat and its preparation method and application
By using a low-temperature base glaze formula for cast iron enamel that is free of fluoride and nitrate salts and utilizing recycled ternary battery cathode materials, the problems of fluoride emissions and nitrate pollution in enamel glazes have been solved, achieving environmental protection and performance improvement while reducing costs.
Patent Information
- Application Number
- CN202511714020.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-21
- Publication Date
- 2026-02-06
- Estimated Expiration
- 2045-11-21
AI Technical Summary
The use of fluoride and nitrate salts in existing enamel glazes leads to environmental pollution and health risks, and makes it difficult to meet the requirements of the EU REACH regulation. Meanwhile, alternatives have functional defects and high costs.
The low-temperature base glaze formula for cast iron enamel, which is free of fluoride salts and nitrates, uses recycled ternary battery cathode materials as the main component, combined with raw materials such as quartz, anhydrous borax, and soda ash. It is formed by low-temperature melting and rapid cooling processes to create a borosilicate glass body, which is then applied to the cast iron substrate.
It achieves ultra-low fluoride emissions, meets EU REACH regulations, solves the problem of clogging in environmental protection equipment, improves adhesion performance and low-temperature firing adaptability, reduces heavy metal costs, and extends equipment operating cycle.
Smart Images

Figure CN121159101B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the field of enamel technology, and particularly relates to a cast iron enamel low-temperature ground glaze free of fluorinated salt and nitrate salt as well as a preparation method and application thereof. BACKGROUND
[0002] As a transition layer between the metal substrate and the face glaze, the adhesion and firing performance of the enamel ground glaze directly affect the product quality, and the green environmental protection affects the survival and sustainable development of the industry. In the traditional enamel ground glaze formula, fluorinated salt (such as fluorite, sodium fluorosilicate) (accounting for 1-15%) is usually added as a fluxing agent and adhesion enhancer. The fluorinated salt is not an "optional" additive in the traditional enamel ground glaze, but an "indispensable" skeleton component. It lays the foundation for the firm combination of the glaze and the metal substrate from the physical and chemical dimensions through multiple synergies such as reducing the melting temperature, forming an alloy layer by corroding the interface, creating a mechanical anchoring effect, improving opalescence and wettability. Simply and roughly removing the fluorinated salt is equivalent to removing the load-bearing wall of the building, which does not lead to a "decrease" in performance, but a "collapse" of the entire enamel system. Any attempt to eliminate fluorinated salt must be based on the discovery or invention of a new substance or new process system that can completely simulate or replace the above-mentioned multiple functions, and this has so far been a major technical challenge in the enamel process field. Therefore, the importance of fluorinated salt in the traditional process cannot be overstated. However, research has shown that:
[0003] 1. Hydrogen fluoride (HF) and silicon tetrafluoride (SiF4) gases released during high-temperature melting process cause harm to health and the environment.
[0004] 2. The European Union's REACH regulation lists fluorides as substances of very high concern (SVHC), and products containing fluorinated salt cannot meet the EU's REACH regulation requirements for fluorine, with a fluorine (F) limit of 20 mg / kg.
[0005] 3. End environmental management equipment is blocked due to fluorinated salt crystallization, severely restricting normal production of enterprises.
[0006] At the same time, nitrate salt, as a traditional oxidizing agent and adhesion promoting component, is prone to produce nitrogen oxides (NO x ) during high-temperature decomposition, also facing environmental pressure. Currently, the removal of nitrate from enamel glaze has solved the problem of nitrogen oxide emissions (such as CN114368912B, CN114315150B, CN114315151B, etc.), and further development of a fluorine-free and nitrate-free system is not only a necessary choice to respond to regulations, but also a forward-looking technical layout for the future.
[0007] The replacement of fluorinated salt is a major technical bottleneck at present, mainly reflected in:
[0008] (1) Fluorinated salt dependence is strong, and environmental risk is prominent: CN119710693A (high-temperature-resistant enamel glaze) uses cryolite (Na3AlF6) as a fluxing agent, although it improves temperature resistance, but does not solve the problem of fluorine emission; CN112342544A (low-temperature acid and alkali-resistant cast iron enamel) contains sodium fluoride (5-7 parts) in the face glaze formula.
[0009] (2) Non-fluorine substitution scheme has functional defects: CN105800935A (enamel underglaze material) attempts to use lanthanide oxides to enhance adhesion, but it still needs to add 8% fluorine to assist melting, and the high cost of rare earth makes it difficult to promote. CN116854374A (black enamel composite glaze) uses a cobalt-nickel underglaze system, but the anti-explosive agent used contains 8-10% fluorite powder.
[0010] (3) The field of ceramics involves fluorine-free schemes, but it is difficult to migrate applications: CN110885189A relates to a zirconium-free lanolin enamel and a positioning crystal flower ceramic tile made using the same, CN115626774A relates to a soft light skin ceramic rock plate and a preparation method thereof, CN112979271A relates to a preparation method of a light-weight high-strength pure-color glaze tile, and CN118754723A relates to a hydrophilic self-cleaning antique tile based on phase separation and a preparation method thereof. Although the above-mentioned prior art does not involve the use of fluorinated salt, its technical essence belongs to the field of building ceramic glaze, which is different from the field of enamel underglaze. There are essential differences between ceramic glaze and metal-based enamel glaze in terms of thermal expansion coefficient (the difference in expansion coefficient between the two is one order of magnitude), firing temperature (the firing temperature of ceramic glaze is higher than that of enamel glaze by more than 200°C), and bonding mechanism (the body of ceramic glaze is porcelain clay, while the body of enamel glaze is metal), thus it cannot be directly applied to the field of metal-based enamel.
[0011] In summary, on the basis of denitrification, the problem of defluorination is solved, and the quality of enamel products is improved, which has very important practical significance for promoting the green, low-carbon and high-quality development of the enamel industry. SUMMARY
[0012] In view of the excessive emission of fluorides in the production process of existing enamel glaze, which causes damage to health and the environment, the fluorinated salt-containing products cannot meet the requirements of the EU REACH regulation on fluorine, and the emitted fluorinated salt blocks environmental management facilities, which seriously restricts the normal production of enterprises, the present application provides a cast iron enamel low-temperature underglaze without fluorinated salt and nitrate, as well as a preparation method and application thereof.
[0013] The low-temperature base glaze for cast iron enamel, which is free of fluoride salts and nitrates, of the present invention is composed of the following components in parts by weight: 12-14 parts quartz, 29-31 parts anhydrous borax, 9-11 parts soda ash, 6-9 parts potassium carbonate, 8-9 parts barium carbonate, 24-26 parts potassium feldspar, 1.2-1.6 parts magnesium carbonate, 0.5-0.6 parts copper oxide, 1.2-1.4 parts manganese oxide, 0.8-0.9 parts aluminum oxide, and 2.2-3.4 parts recycled ternary lithium battery cathode material, wherein the recycled ternary lithium battery cathode material is a powder material containing lithium, nickel, cobalt, and manganese obtained by recycling waste ternary lithium battery cathode material.
[0014] Further, the composition includes 13-13.5 parts quartz, 29.5-30 parts anhydrous borax, 10-11 parts soda ash, 6.5-8 parts potassium carbonate, 8.5-9 parts barium carbonate, 24-25 parts potassium feldspar, 1.2-1.4 parts magnesium carbonate, 0.5-0.6 parts copper oxide, 1.2-1.3 parts manganese oxide, 0.8-0.9 parts aluminum oxide, and 2.8-3.2 parts recycled ternary battery cathode material.
[0015] Furthermore, the mass percentage of SiO2 in quartz is ≥99%, the mass percentage of SiO2 in potassium feldspar is ≥71%, and the mass percentage of K2O+Na2O is ≥11%. In the recycled ternary battery cathode material, based on the percentage of metal mass to the total mass of the material, Co ≥12.5wt%, Ni ≥30.2wt%, Mn ≥12.2wt%, Li ≥5.9wt%, and other raw materials are of industrial grade purity.
[0016] Furthermore, the recycled ternary battery cathode material is a commercially available material that meets the aforementioned percentage content of lithium, nickel, cobalt, and manganese. Other impurities do not affect the performance and use of the base glaze.
[0017] The preparation method of the above-mentioned low-temperature base glaze for cast iron enamel that is free of fluoride salts and nitrates includes the following steps:
[0018] (1) Weigh each component raw material according to the above mass proportions;
[0019] (2) Stir and mix the raw materials described in step (1) until they are evenly mixed;
[0020] (3) Add the mixed material into the melting furnace for melting. The melting furnace is in a pure oxygen environment and the temperature is controlled at 1230±10℃.
[0021] (4) After the material described in step (3) is completely melted, a borosilicate glass body is obtained. The molten borosilicate glass body is then drilled and quickly drawn into a glass wire of 1.2 to 1.5 meters for testing. The testing requirement is that the glass wire is completely melted within 1 meter.
[0022] (5) the borosilicate glass body is quenched, and the product is obtained.
[0023] Further, in step (5), the quenching is performed by using a water quenching or tabletting process.
[0024] The application of the cast iron enamel low-temperature base glaze without fluorinated salt and nitrate salt is applied to a blank with a cast iron base body, and the firing temperature of the finished product is 740-760 DEG C.
[0025] The application introduces the recycled ternary battery positive material into the cast iron enamel low-temperature base glaze formula, not only significantly enhances the adhesion of the base glaze, but also strengthens the synergistic effect between the components, and promotes the improvement of the base glaze porcelain surface, gloss and other performances.
[0026] The application has the following beneficial effects:
[0027] (1) The fluorinated salt is discharged in an ultra-low standard;
[0028] (2) The product is detected by SGS, and the fluorinated salt detection result shows that it is not detected, which meets the limit value requirement of the SVHC (high concern substance) of the EU REACH regulation.
[0029] (3) The end environmental protection equipment blockage problem is solved: by completely removing the fluorinated salt (fluorite, sodium fluorosilicate, etc.), the fluorinated salt crystallization source is eliminated from the source, and the end environmental protection equipment blockage problem is solved. According to the actual measurement of the production line, the continuous operation period of the equipment is prolonged from the original 10-15 days to more than 180 days, and the maintenance cost is significantly reduced.
[0030] (4) The core performance of the base glaze is not attenuated: through the adhesion enhancement effect of the recycled ternary battery positive material instead of the fluorinated salt, the adhesion level is tested to be 1-2 level (the traditional fluorine-containing base glaze is 1-2 level).
[0031] (5) Low-temperature firing adaptability: the eutectic composite fluxing system (multi-element carbonate + borate) interacts with other components, so that the firing temperature is stably controlled at 740-760 DEG C, and the porcelain layer flow flatness and bubble elimination rate are equivalent to those of the fluorine-containing base glaze.
[0032] (6) Resource recycling and cost optimization: the use of recycled ternary battery positive material not only reduces the cobalt-nickel-lithium raw material cost by more than 25%, but also avoids heavy metal waste pollution. BRIEF DESCRIPTION OF DRAWINGS
[0033] Figure 1 The photo of the enamel plate made of cast iron for the product obtained in example 1 of the application. DETAILED DESCRIPTION
[0034] The application will be further described in detail in combination with specific embodiments, but the application is not limited thereto.
[0035] The equipment used in the embodiment of the application is as follows:
[0036] Batching: a full-automatic batching and mixing system is adopted. The system is fully automatic computer controlled, and has the characteristics of accurate weighing, uniform mixing and high batching efficiency.
[0037] Melting: an automatic feeding system, an automatic pure oxygen combustion control system and an automatic discharging system are adopted.
[0038] Packaging: an automatic packaging system is adopted.
[0039] In addition to the recovered ternary battery positive electrode material, the purity of the raw materials used in the embodiment of the application meets the requirements of the industrial grade.
[0040] Embodiment 1
[0041] (1) The raw materials are weighed according to the mass parts of each component as follows:
[0042] Quartz 12 parts, zero-water borax 29 parts, soda ash 9 parts, potassium carbonate 8 parts, barium carbonate 9 parts, potassium feldspar 26 parts, magnesium carbonate 1.2 parts, copper oxide 0.6 parts, manganese oxide 1.2 parts, aluminum oxide 0.8 parts, and recovered ternary battery positive electrode material 3.2 parts.
[0043] The mass proportion of SiO2 in quartz is ≥99%, the mass proportion of SiO2 in potassium feldspar is ≥71%, K2O+Na2O is ≥11%, and in the recovered ternary battery positive electrode material, the metal mass percentage in the total mass of the material is Co≥12.5 wt%, Ni≥30.2 wt%, Mn≥12.2 wt%, and Li≥5.9 wt%, and the other raw materials are of industrial purity.
[0044] (2) The above raw materials are stirred and mixed uniformly.
[0045] (3) The uniformly mixed material is added to a melting furnace for melting. Pure oxygen is used in the melting furnace during melting, and the temperature is controlled at 1230±10℃ for melting.
[0046] (4) After the above material is completely melted, a borosilicate glass body is obtained. The molten borosilicate glass body is drilled and quickly drawn into a 1.2-1.5 meter glass filament for detection. The detection requirement is that there is no knot within 1 meter of the glass filament, which means that the melting is complete.
[0047] (5) The melted borosilicate glass body is water quenched, and the product is obtained.
[0048] The photo of the product obtained in Embodiment 1 applied to a porcelain enamel plate made of cast iron is as follows: Figure 1The low temperature enamel enamel surface of the cast iron enamel enamel is smooth and delicate, and the low temperature sintering performance and adhesion performance are excellent, and is widely applied to cast iron enamel products.
[0049] Example 2
[0050] The preparation process of this example is basically the same as that of example 1, except that the mass parts of each component in step (1) are: quartz 13.5 parts, anhydrous borax 29.5 parts, soda ash 9.5 parts, potassium carbonate 6.5 parts, barium carbonate 9 parts, potassium feldspar 25.4 parts, magnesium carbonate 1.6 parts, copper oxide 0.5 parts, manganese oxide 1.4 parts, aluminum oxide 0.8 parts, and recovered ternary battery positive material 2.8 parts.
[0051] Example 3
[0052] The preparation process of this example is basically the same as that of example 1, except that the mass parts of each component in step (1) are: quartz 14 parts, anhydrous borax 30 parts, soda ash 10 parts, potassium carbonate 9 parts, barium carbonate 8 parts, potassium feldspar 24 parts, magnesium carbonate 1.4 parts, copper oxide 0.5 parts, manganese oxide 1.3 parts, aluminum oxide 0.8 parts, and recovered ternary battery positive material 2.2 parts.
[0053] Example 4
[0054] The preparation process of this example is basically the same as that of example 1, except that the mass parts of each component in step (1) are: quartz 13 parts, anhydrous borax 31 parts, soda ash 11 parts, potassium carbonate 6 parts, barium carbonate 8.5 parts, potassium feldspar 25 parts, magnesium carbonate 1.4 parts, copper oxide 0.5 parts, manganese oxide 1.2 parts, aluminum oxide 0.9 parts, and recovered ternary battery positive material 3.4 parts.
[0055] Comparative Example 1
[0056] The rest is the same as example 1, except that the mass parts of each component in step (1) are: quartz 12.9 parts, anhydrous borax 29 parts, soda ash 9 parts, barium carbonate 8 parts, potassium feldspar 23 parts, magnesium carbonate 1.2 parts, copper oxide 0.5 parts, manganese oxide 1.2 parts, aluminum oxide 0.8 parts, sodium fluorosilicate 7.2 parts, lithium carbonate 2 parts, cobalt oxide 1.2 parts, and nickel oxide 0.5 parts.
[0057] The test results of the products obtained in the above examples and comparative examples are shown in Table 1 below.
[0058] Table 1 Test results of products obtained in examples and comparative examples
[0059]
[0060] The above examples and detection results prove that the cast iron enamel low-temperature base glaze produced by the method of the application does not contain fluorinated salt and nitrate, no fluorinated salt is generated in the preparation process, the properties (porcelain surface, gloss, adhesion, sintering temperature) of the obtained product meet the requirements of cast iron enamel low-temperature base glaze, the fluorinated salt detection result of the product shows that no fluorinated salt is detected, the limit requirement of SVHC (substance of very high concern) of the European Union REACH regulation is met, and the technical problems of environmental pollution caused by fluorinated gas emission and fluorinated salt emission in the production process of the existing cast iron enamel low-temperature base glaze and the blockage of environmental protection treatment facilities are fundamentally solved.
Claims
1. A cast iron enamel low temperature ground enamel free of fluorinated salts and free of nitrates, characterized in that, The formula is composed of the following components in mass parts: quartz 12-14 parts, zero-water borax 29-31 parts, soda ash 9-11 parts, potassium carbonate 6-9 parts, barium carbonate 8-9 parts, potassium feldspar 24-26 parts, magnesium carbonate 1.2-1.6 parts, copper oxide 0.5-0.6 parts, manganese oxide 1.2-1.4 parts, aluminum oxide 0.8-0.9 parts, and recycled ternary battery positive electrode material 2.2-3.4 parts, wherein the recycled ternary battery positive electrode material is a powder material containing lithium, nickel, cobalt and manganese recovered from waste ternary lithium battery positive electrode material.
2. The fluoro-salt and nitrate-free cast iron enamel low temperature ground enamel according to claim 1, characterized in that, Quartz 13-13.5 parts, zero-water borax 29.5-30 parts, soda ash 10-11 parts, potassium carbonate 6.5-8 parts, barium carbonate 8.5-9 parts, potassium feldspar 24-25 parts, magnesium carbonate 1.2-1.4 parts, copper oxide 0.5-0.6 parts, manganese oxide 1.2-1.3 parts, aluminum oxide 0.8-0.9 parts, and recycled ternary battery positive electrode material 2.8-3.2 parts.
3. The fluoro-salt-free and nitrate-free cast iron enamel low temperature ground enamel according to claim 1 or 2, characterized in that, In the recycled ternary battery positive electrode material, the mass percentage of Co, Ni, Mn and Li in the total mass of the material is Co≥12.5 wt%, Ni≥30.2 wt%, Mn≥12.2 wt%, and Li≥5.9 wt%.
4. The fluoro-salt-free and nitrate-free cast iron enamel low temperature ground enamel according to claim 1 or 2, characterized in that, The mass percentage of SiO2 in the quartz is ≥99%.
5. The fluoro-salt-free and nitrate-free cast iron enamel low temperature ground enamel according to claim 1 or 2, characterized in that, The mass percentage of SiO2 in the potassium feldspar is ≥71%, and the mass percentage of K2O+Na2O is ≥11%.
6. A process for the production of a non-fluoride and non-nitrate salt free cast iron enamel low temperature ground enamel according to any one of claims 1 to 5, characterized in that, The method comprises the following steps: (1) weighing each component raw material; (2) stirring and mixing the raw materials in step (1) uniformly; (3) melting the uniformly mixed material in a melting furnace, using pure oxygen environment in the melting furnace, and controlling the temperature at 1230±10℃; (4) obtaining a borosilicate glass body after the material in step (3) is completely melted, tapping the molten borosilicate glass body, and quickly drawing it into a 1.2-1.5 meter glass filament for detection, wherein the detection requirement is that there is no knot within 1 meter of the glass filament, indicating that the melting is complete; (5) rapidly cooling the melted borosilicate glass body to obtain the product.
7. The production method according to claim 6, wherein In step (5), the rapid cooling is achieved by water quenching or tablet pressing process.
8. Use of a cast iron enamel low temperature ground enamel free of fluorinated salts and nitrates according to any one of claims 1 to 5, characterized in that, When applied to a cast iron-based blank, the firing temperature of the finished product is 740-760℃.
Citation Information
Patent Citations
Base enamel material, preparation method and application
CN105800935A
Zirconium-free mutton fat glaze and positioning crystal pattern ceramic tile prepared from the same
CN110885189A
Low-temperature acid and alkali resistant cast iron enamel processing technology and coating formula
CN112342544A
Nitrate-free environmentally friendly steel plate enamel low-temperature acid-resistant transparent glaze and preparation method thereof
CN114315150B
Nitrate-free environmentally friendly cast iron enamel transparent glaze and preparation method thereof
CN114315151B